2005
DOI: 10.1002/lt.20464
|View full text |Cite
|
Sign up to set email alerts
|

Response to an experimental HBV vaccine permits withdrawal of HBIg prophylaxis in fulminant and selected chronic HBV-infected liver graft recipients

Abstract: See Editorial on Page 1181Strategies using lamivudine and hepatitis B immunoglobulins (HBIg) for prevention of hepatitis B virus (HBV) reinfection after liver transplantation (LT) are expensive since life-long treatment is needed. We evaluated the possibility to obtain protective hepatitis B surface antigen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 25 publications
2
46
1
4
Order By: Relevance
“…[8][9][10][11] Active immunization with standard hepatitis B vaccines in these patients is considered a promising substitute to the current treatment strategy, although the results of this new strategy have been controversial. [12][13][14][15][16][17][18][19][20][21][22] Some studies have reported that responders to hepatitis B vaccination, defined as patients with anti-HBs, should stop taking HBIG and/or antiviral agents. 12,16,17,[20][21][22] However, the safety of discontinuing HBIG and/or antiviral agents in responders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Active immunization with standard hepatitis B vaccines in these patients is considered a promising substitute to the current treatment strategy, although the results of this new strategy have been controversial. [12][13][14][15][16][17][18][19][20][21][22] Some studies have reported that responders to hepatitis B vaccination, defined as patients with anti-HBs, should stop taking HBIG and/or antiviral agents. 12,16,17,[20][21][22] However, the safety of discontinuing HBIG and/or antiviral agents in responders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22] Some studies have reported that responders to hepatitis B vaccination, defined as patients with anti-HBs, should stop taking HBIG and/or antiviral agents. 12,16,17,[20][21][22] However, the safety of discontinuing HBIG and/or antiviral agents in responders remains unclear. In the present study, we investigated intrahepatic and extrahepatic HBV total DNA and ccc DNA in responders to active hepatitis B immune reconstitution who had discontinued HBIG and/or antiviral agents and in non-responders to active hepatitis B immune reconstitution.…”
Section: Introductionmentioning
confidence: 99%
“…Eine aktive Hepatitis B Impfung nach LT mit dem Ziel eine dauerhafte anti-HBs Antwort zu induzieren, ist nur bei wenigen Patienten möglich [102][103][104][105], kann jedoch im Einzellfall unter Beibehaltung der Kombinationsprophylaxe in Erwägung gezogen werden.…”
Section: Reinfektionsprophylaxeunclassified
“…Durch den Zusatz immunstimulatorischer Adjuvanzien und/oder den Einsatz einer rekombinanten HBV-Vakzine der dritten Generation unter Einschluss der S-, Prä-S1-und Prä-S2-Proteine konnte eine deutlich bessere Responserate bei LTX-Patienten erzielt werden [71][72][73]. Eine rekombinante Prä-S-Protein enthaltende HBV-Vakzine wurde auch von einer Gruppe in Hongkong, China, bei transplantierten HBV-Patienten eingesetzt (jeweils 40 μg i.m.…”
Section: Neues Aus Studien Mit Hbvimpfstoffen Hoher Immunogenitätunclassified